The Mediation Dilemma of (Not) Talking to Terrorists. Issue 4 (4th November 2020) - Haspeslagh, Sophie
Abstract: Not long ago, it was accepted practice to 'talk to whomever you need to talk to for peace'. Then the idea that you cannot talk to 'terrorists' took hold. The article explores norm contestation, what happens when hard norms interact with softer norm even when they are settled and central to mediation practice. The article traces the emergence, development and interaction of these two contradictory norms in key United Nations documents and discussions since 1945. It also triangulates this content analysis with personal interviews with UN mediators and perspectives from international non‐governmental mediators. The article argues that over the last 20 years the embedding of proscription regimes in the multilateral system has deeply re‐shaped fundamental norms underlying mediation such as impartiality, inclusivity and the idea that mediators should be able to speak to everyone to protect human lives.